Lack of association between pandemic chilblains and SARS-CoV-2 infection - Gehlhausen, Jeff R.; Little, Alicia J.; Ko, Christine J.; Emmenegger, Marc; Lucas, Carolina; Wong, Patrick; Klein, Jon; Lu, Peiwen; Mao, Tianyang; Jaycox, Jillian; Wang, Eric; Ugwu, Nelson; et al. (Proceedings of the National Academy of Sciences - PNAS, 2022)
An increased incidence of chilblains has been observed during the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic and attributed to viral infection. Direct evidence of this relationship has been limited, however, as most cases do not have molecular evidence of prior SARS-CoV-2 infection with PCR or antibodies. We enrolled a cohort of 23 patients who were diagnosed and managed as having SARS-CoV-2–associated skin eruptions (including 21 pandemic chilblains [PC]) during the first wave of the pandemic in Connecticut. Antibody responses were determined through endpoint titration enzyme-linked immunosorbent assay and serum epitope repertoire analysis. T cell responses to SARS-CoV-2 were assessed by T cell receptor sequencing and in vitro SARS-CoV-2 antigen-specific peptide stimulation assays. Immunohistochemical and PCR studies of PC biopsies and tissue microarrays for evidence of SARS-CoV-2 were performed. Among patients diagnosed and managed as “covid toes” during the pandemic, we find a percentage of prior SARS-CoV-2 infection (9.5%) that approximates background seroprevalence (8.5%) at the time. Immunohistochemistry studies suggest that SARS-CoV-2 staining in PC biopsies may not be from SARS-CoV-2. Our results do not support SARS-CoV-2 as the causative agent of pandemic chilblains; however, our study does not exclude the possibility of SARS-CoV-2 seronegative abortive infections.